Remembering the Future: Science Fiction and the Emerging Art of Dialogue Theology - Christie, James (My University, 2013)
Dialogue Theology, established in June of 2012 as an interdisciplinary stream in the Master of Arts in Spiritual Disciplines and Ministry Practices in the Faculty of Theology of The University of Winnipeg, may best be defined as “the art and discipline of bringing Christian theology into intentional conversation with other religions and worldviews for the sake of ‘mending the world.’” Dialogue theology is inspired by the groundbreaking work of luminaries in the mold of Huston Smith and Karen Armstrong, and by pivotal thinkers of the stature of Hannah Arendt who wrote, “We are most human when we are in dialogue.” The intersection of science fiction, ethics and theology/religious studies is obvious: science fiction is the closest modern and postmodern analogy to biblical prophecy extant. From Heinlein’s “If This Goes On . . .” to Herbert’s Dune to McCarthy’s The Road, the references are legion. In addition to this inherent prophetic tendency, Robert Sawyer has enhanced the dialogue around the question, “What does it mean to be human?” Rarely has one practitioner addressed so cogent a theme in so many intriguing, engaging and significant ways. From our deep roots in Hominids, Humans and Hybrids to a startling future in Calculating God; from the quandaries of the techno-human spectrum in Mind Scan to the evolution of intelligence in Wake, Watch and Wonder, Sawyer opens up new dimensions of dialogue with science and society for the theologian. This paper will employ Sawyer’s work in an attempt to advance the observation of Sri Jawaharlal Nehru at the opening of the then Ceylon Academy of Science in 1961, that “The time is past for politics and religion; the time has come for science and spirituality.”
Keywords: science fiction; Robert Sawyer; dialogue theology; Christian theology